PENGARUH KOMPETENSI PEREKAM MEDIS DAN INFORMASI KESEHATAN TERHADAP PELAYANAN PASIEN RAWAT JALAN DI KLINIK PRATAMA MULYA SEHAT ANTAPANI BANDUNG - Renaldy Firman Pratama (Jurnal Infokes, 2021)
This research was conducted with of knowing the competency analysis of medical records and information on the severity of outpatient service at Mulya Sehat Antapani Bandung Clinic. The research method used is a qualitative method with a descriptrive approach. Data collection techniques used were observation, interviews, and literature study. Based on the result of research on the knowing competency of medical records and health information on service for outpatients at Mulya Sehat Antapani Bandung Clinic, that the waiting time for outpatient registration services after taking the queue number is long enough to wait and patient satisfaction with services. Quality is quite satisfied. From the research conducted there were several problems, including : (1) Incomplete filling of patient identity data in outpartient registration. (2) The existence of multiple patient medical record numbers or multiple medical record numbers. The suggestion given to the hospital include : (1) Mulya Sehat Clinic are advised to provide direction, coordination and evaluation to outpatient service coordinators in order to further enhance cooperation among registration officer regarding the importance of accuracy in outpatient registration and frequenct rechecking after filling in patient social data at registration. (2) It is better if the hospital should further increase the importance of checking the medical record files again and for outpatient registration officers to be more careful and observant in entering new patients in the data. Specially outpatient income for old patients so that there are no more double medical records.